Outcomes and Contemporary Trends in Surgical vs Transcatheter Aortic Valve Replacement in Patients with Chronic Obstructive Pulmonary Disease. Issue 4 (4th July 2021) - Khan, Muhammad Zia; Alharbi, Anas A.; Zahid, Salman; Khan, Muhammad U.; Ullah, Waqas; Sattar, Yasar; Rashid, Muhammad; Kichloo, Asim; Munir, Muhammad Bilal; Balla, Sudarshan
ABSTRACT: Background: Chronic obstructive lung disease (COPD) is a common morbidity among patients referred for aortic valve replacement. The objective of the present study is to assess trends and outcomes of COPD patients undergoing either transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (SAVR) for severe aortic stenosis. Methods: We analyzed the National Inpatient Sample database from January 2012 to December 2017 using the International Classification of Diseases, 9th and 10th Revision Clinical Modifications to identify all patients with COPD aged ≥50 years who underwent either TAVR or SAVR for aortic stenosis. To account for potential bias, 1:1 propensity-matched analysis was performed. Logistic regression was used for predictors of mortality in the cohort. Linear regression was used for trend analysis. Results: Of the total of 95, 555 cases, 40, 080 underwent TAVR whereas 49, 985 underwent SAVR. In-hospital mortality for the propensity-matched cohorts was higher in the SAVR cohort compared to the TAVR group (4.6% vs. 2.5%; p < 0.001). Respiratory complications were also higher in the SAVR group (7.5% vs. 3.7%; p < 0.001) but were less likely to have a permanent pacemaker placement (5.3% vs. 10.8%, p < 0.001). Length of stay (11.8 days [standard deviation (SD), 8.8] vs. 6.4 days [SD, 6.8]) and cost of stay ($244, 657 [SD, $183, 333] vs. $229, 524 [SD, $146, 994]) were favorable toward TAVR as compared to SAVR. In-hospital mortality has declined over the study period in the TAVR group from 4.8% to 1.5%. Conclusion: TAVR has more favorable in-hospital outcomes in patients with COPD compared to SAVR.